Inhibition of Histone H3K9 Methylation by BIX-01294 Promotes Stress-Induced Microspore Totipotency and Enhances Embryogenesis Initiation - Berenguer, Eduardo; Bárány, Ivett; Solís, María-Teresa; Pérez-Pérez, Yolanda; Risueño, María C.; Testillano, Pilar S. (Frontiers in Plant Science, 2017)
Microspore embryogenesis is a process of cell reprogramming, totipotency acquisition and embryogenesis initiation, induced in vitro by stress treatments and widely used in plant breeding for rapid production of doubled-haploids, but its regulating mechanisms are still largely unknown. Increasing evidence has revealed epigenetic reprogramming during microspore embryogenesis, through DNA methylation, but less is known about the involvement of histone modifications. In this study, we have analyzed the dynamics and possible role of histone H3K9 methylation, a major repressive modification, as well as the effects on microspore embryogenesis initiation of BIX-01294, an inhibitor of histone methylation, tested for the first time in plants, in Brassica napus and Hordeum vulgare. Results revealed that microspore reprogramming and initiation of embryogenesis involved a low level of H3K9 methylation. With the progression of embryogenesis, methylation of H3K9 increased, correlating with gene expression profiles of BnHKMT SUVR4-like and BnLSD1-like (writer and eraser enzymes of H3K9me2). At early stages, BIX-01294 promoted cell reprogramming, totipotency and embryogenesis induction, while diminishing bulk H3K9 methylation. DNA methylation was also reduced by short-term BIX-01294 treatment. By contrast, long BIX-01294 treatments hindered embryogenesis progression, indicating that H3K9 methylation is required for embryo differentiation. These findings open up new possibilities to enhance microspore embryogenesis efficiency in recalcitrant species through pharmacological modulation of histone methylation by using BIX-01294.